SOCIO-ECONOMIC CHALLENGES FOR REGIONS AND AGRICULTURE IN THE NEW MEMBER-STATES - Rositsa BELUHOVA-UZUNOVA; Mariyana SHISHKOVA; Krum HRISTOV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The regional inequalities in the EU are an essential part of policy agenda and public discussions. The new Member-States remain in the group of "lagging regions" that includes low-income areas facing a number of challenges. Agriculture is a crucial sector in most of these regions, and it is seen as a major source of local employment and income. The survey aims to present the characteristics and the implication of regional disparities and outline recommendations for more balanced development. The study shows that diverge is growing at a national, regional and local level. Regions are experiencing low growth, high unemployment rate, social exclusion and poverty. However, it can be concluded that many of the regions have unexplored potential. In order to address the disparities, then policymakers should focus on the regions' specific features. The regional programs should be directed to their unique characteristics and challenges. In this regard, the implementation of targeted support should be associated with coordination and cooperation between different stakeholders.